CRYOPRESERVATION OF MENTHA PIPERITA L. GERMPLASM AND CONFIRMATION OF GENETIC STABILITY AFTER CRYO-STORAGE - S. Galatali; M. Ceylan; E. Ogur; N. Adanacioglu; E. Kaya (Journal of Animal and Plant Sciences, 2023)
Peppermint is an important aromatic-medicinal plant species and it has valuable essential oil contents such as menthol, linalool and limonene. The main purpose of the current study was to optimize a protocol for cryopreservation of M. piperita local cultivars (G-74, Candarli and Gomec). The secondary aim was to investigate the genetic stability after cryopreservation using ISSR marker system. Three different single step freezing techniques were compared for long-term preservation of these local cultivars and the optimum regeneration percentages were acquired by using the droplet vitrification technique. The PVS2 treatments of this technique showed succesful long-term preservation of M. piperita cultivars with regeneration percentages of 72% to Candarli cultivar (60 min PVS2), 52% to Gomec cultivar (75 min PVS2) and 62.5% to G-74 cultivar (30 min PVS2) respectively. The ISSR PCR results showed that the genetic stability from cryopreserved M. piperita cultivars were high. While genetic stability percentage was ~99% for the Candarli cultivar, for the Gomec and G-74 cultivars the genetic fidelity was100%. The shoots that come from the cryopreserved shoot tips showed normal and health rooting, and all of them were also easily adapted to greenhouse conditions.
Keywords: DMSO; encapsulation; ISSR-PCR; PVS2; vitrification